2000
DOI: 10.1002/(sici)1097-4660(200003)75:3<187::aid-jctb206>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Growth of naturally occurring microbial isolates in metal-citrate medium and bioremediation of metal-citrate wastes

Abstract: The use of citrate as a chelating agent in decontamination operations is of environmental concern as it can mobilize toxic heavy metals if discharged into the environment. Many heavy metalcitrate complexes are recalcitrant to biodegradation. Citrate-utilizing strains of Pseudomonas aeruginosa and Pseudomonas putida were isolated from a mixed culture which had been maintained with EDTA as the carbon source for 2 years. Citrate (5 mM) was used as the sole carbon source in medium supplemented with 5 mM Cd, Zn, Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Above pH 8, the complex exists in a tridentate form involving the hydroxyl group of citrate, and above pH 9, it exists in a polymeric form [Ni 4 (OH)Cit 3 ] 5À (Still and Wikberg, 1980;Strouse et al, 1977 complex can be biodegraded by bacteria; however, the tridentate and polymeric Ni-citrate complexes are recalcitrant to biodegradation (Francis et al, 1996). In a medium containing Ni and citrate in a ratio of 1:1, 95 and 100% of the citrate was utilized by Pseudomonas aeruginosa and P. putida, respectively, and the addition of inorganic phosphate as a precipitant promoted Ni removal effectively (Thomas et al, 2000). Francis et al (1996) observed that 70% of the Ni-citrate complexes were degraded by P. fluorescens in medium with a 1:1 Ni:citrate content and buffered at pH 6.1, and that the addition of Fe 3+ significantly promoted the degradation of Ni-citrate complex and removal of Ni from solution.…”
Section: Introductionmentioning
confidence: 99%
“…Above pH 8, the complex exists in a tridentate form involving the hydroxyl group of citrate, and above pH 9, it exists in a polymeric form [Ni 4 (OH)Cit 3 ] 5À (Still and Wikberg, 1980;Strouse et al, 1977 complex can be biodegraded by bacteria; however, the tridentate and polymeric Ni-citrate complexes are recalcitrant to biodegradation (Francis et al, 1996). In a medium containing Ni and citrate in a ratio of 1:1, 95 and 100% of the citrate was utilized by Pseudomonas aeruginosa and P. putida, respectively, and the addition of inorganic phosphate as a precipitant promoted Ni removal effectively (Thomas et al, 2000). Francis et al (1996) observed that 70% of the Ni-citrate complexes were degraded by P. fluorescens in medium with a 1:1 Ni:citrate content and buffered at pH 6.1, and that the addition of Fe 3+ significantly promoted the degradation of Ni-citrate complex and removal of Ni from solution.…”
Section: Introductionmentioning
confidence: 99%
“…At that point in time, the concentration of copper in the biofilm was already nearly 14 times higher than that of the medium (2.82 mg g Ϫ1 compared with 0.192 mg g Ϫ1 ). Citrate likely played an important role in the quick penetration of Cu into the biofilm, since metal-citrate transport systems have been identified in many bacteria (21) and P. putida has been found to use metalcitrate complexes as carbon sources (33). The high percentage (52.6 to 61.4%) of citrate-Cu-like species in the biofilm confirms that copper was primarily complexed with citrate in P. putida CZ1 biofilms.…”
Section: Discussionmentioning
confidence: 90%
“…Degradation of the citrate metal complex would have resulted in the release of copper ion, which would have then been free to interact with phosphate, thereby causing precipitation and a reduction in the toxicity of copper (1). P. putida has been found to precipitate Co and Ni as metal phosphates when utilizing Co/Nicitrate complexes (33). Protection of biofilm cells by precipitation has also been reported in mixed sulfate-reducing bacteria biofilms, where Cu was precipitated at the biofilm surface or in the liquid phase as Cu-sulfide (37).…”
Section: Figmentioning
confidence: 99%
“…The mechanism is postulated to proceed according to the following reactions for the complete citrate utilization in the 1:1:2 Fe:Cd:citrate (1-3) and Zn:Cd:citrate media (4-5). It can be seen from Table 1 that the formation constants of tridentate Fe(III)-citrate and bidentate Zn-citrate complexes were all relatively greater than that of Cd-citrate complex [7,19] …”
Section: Effect Of Fe 3+ or Zn 2+ On Biotransformation Of Cd-citrate mentioning
confidence: 98%